(untitled) (Comprehensive Journal of Science, 2026)
Libya is one of the rich developing countries out of oil revenues. The discovery of oil contributed to a dramatic change and a burden on all public utilities and facilities, especially the transportation system. Increased traffic congestion, road accidents on intercity highways, and environment pollution have been the negative impacts. The time is ripe for a policy improve intercity public transport. This study aims to focus on some of those issues like rise in private vehicle ownerships, traffic congestion, and demand of more public transport, parking, road safety and air pollution. All of these factors are dependent on each other. So, rectifying one by one will alleviate the major concerns of traffic congestion and other environmental hazards. When each of these factors is addressed the effective contribution can make successful urban development. As traffic grows around the world, congestion becomes more widespread and occurs significantly longer during weekdays. As such congestion and traffic-related pollution are increasingly becoming major issues in cities. The increasing reliance on private transportation, in particular private cars, has created considerable pressure on the road network which consequently has contributed to the problems of traffic congestion. Providing more road spaces to keep pace with traffic demand is not the answer. It would be far too expensive and socially disruptive, and would exacerbate the long term problem which was initially trying to be tackled.